Perancangan Proteksi Inverter Berbasis Arduino Uno - Andre Jason Maabuat; Sherwin R.U.A. Sompie; Meita Rumbayan (Jurnal Teknik Elektro dan Komputer, 2020)
Abstract — Protection system is the safety of electrical equipment in the event of an interruption in the installed system. Inverter one device to convert DC voltage into AC. The use of accumulators and inverters will effective in the event of a power outage in anticipation of a supply voltage, so that the equipment can be reused. Each inverter has a limit on the value of the power that can be used, in this study made a tool that can protect in case of excessive power consumption so that it does not cause components on the inverter to be damaged quickly. One of the results of this research is that the value of this protection device is not far from the wattmeter used as a comparison and for a long time the use of the device to adjusts the battery capacity. Keywords —  Accumulators; Inverters; Protection; Voltage.   Abstrak — Sistem proteksi merupakan pengaman peralatan listrik apabila terjadi suatu gangguan sistem yang terpasang. Inverter salah satu perangkat untuk merubah tegangan DC menjadi AC. Penggunaan akumulator dan inverter efektif apabila terjadi pemadaman listrik sebagai antisipasi suplai tegangan sehingga peralatan dapat digunakan kembali. Setiap inverter mempunyai batas nilai daya yang bisa dipakai, dalam penelitian ini dibuat alat yang dapat memproteksi apabila terjadi pemakaian daya berlebih sehingga tidak menyebabkan komponen pada inverter cepat rusak. Hasil penelitian yang di dapatkan salah satunya nilai dari alat proteksi ini tidak berbanding jauh dari wattmeter yang digunakan sebagai pembanding dan untuk lama penggunaan alat menyesuaikan kapasitas aki. Kata Kunci — Akumulator; Inverter; Proteksi; Tegangan